Central Venous Sinus Thrombosis in a Boy With Acute Severe Ulcerative Colitis - Martín-Masot, Rafael; Ortiz Pérez, Pilar; Serrano Nieto, Juliana; Martínez León, María; Pascual Martínez, Antonia; Blasco-Alonso, Javier; Navas-López, Victor Manuel (Frontiers in Pediatrics, 2019)
Cerebral venous sinus thrombosis (CVST) in childhood is uncommon. Certain diseases predispose patients to CVST, such as inflammatory bowel disease (IBD), which is considered a risk factor for developing thrombosis, which in turn is considered an extraintestinal manifestation of IBD. The use of prophylaxis in certain patients is a controversial topic. We present the case of a 5-year-old child with ulcerative colitis, who presented with transverse sinus thrombosis immediately after colectomy. Considering the recent recommendations on prophylaxis in this disease, our patient and probably many others would benefit from establishing treatment with low-molecular-weight heparin. We believe that these recommendations should be known, with our case serving as an example, given that we are heading in a direction that has so far been controversial.